PENGARUH PROFITABILITAS, TINGKAT PERTUMBUHAN DAN TINGKAT PAJAK TERHADAP STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017 - Heri Enjang Syahputra (JURNAL MUTIARA AKUNTANSI, 2019)
Capital structure is the composition and proportion of long-term debt and equity determined by the company in financing the company. Capital structure decisions can be influenced by several variables. In this study, the author wants to test the effect of variables that affect capital structure including profitability, growth rates and tax rates. The population in this study are Real Estate and Property companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. The number of samples used was 24 companies using a purposive sampling method. The data processing program uses the SPSS (Statistical Product and Service Solution) program. Based on the results of partial tests (t-test) the profitability variable has a tcount of -1,473 while a ttable -2.08596 (tcount > ttable) then H1 is accepted, which means profitability affects the capital structure. The growth rate variable has a tcount of 1,009 while ttable 2.08596 (tcount <ttable) then H2 is rejected, which means that the growth rate has no effect on capital structure. The tax rate variable has a tcount of 0,561 while a ttable of 2.08596 (tcount < ttable) then H3 is rejected, rejected which means that the tax rate has no effect on capital structure. Based on the results of the simultaneous test (F-test) the independent variables has no effect on the capital structure where Fcount < Ftable (1,275 < 3.10).